ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2020–2023 - Robertus Wasa Libu; Agung Slamet Prasetyo (Universitas Nusa Nipa Maumere, 2025)
Timeliness in the submission of financial statements is one of the key indicators of transparency in public companies. This study aims to analyze the effect of profitability, leverage, and firm size on the timeliness of financial statement submission in manufacturing companies within the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the period 2020–2023. The research sample consisted of 17 companies with a total of 51 observations, selected using purposive sampling. Data were analyzed using multiple linear regression. The results show that profitability (ROA) and firm size have a significant positive effect on the timeliness of financial reporting, while leverage (DER) has no significant effect. Simultaneously, profitability, leverage, and firm size have a significant effect, contributing 41.7% to the variation in financial reporting timeliness. This study supports the signaling theory, which states that companies with good performance tend to provide positive signals through compliance with timely reporting.